Strategy-induced organisational resilience through dynamic resource orchestration: Perspectives of former Kenyan bankers - Ahmed, Eltigani; Kilika, James; Gekenia, Clare (International journal of research in business and social science, 2022)
Dynamic Capabilities View (DCV) has an illustrious history of shaping strategic management thinking. However, with the increased frequency of systemic disruption episodes, alternative postulations emerge that promise a more robust explanation for organisational sustainability. The Dynamic Resource Orchestration View (DROV) is the latest evolution in theory development, extending the Dynamic Resource-Based View (DRBV). As a framework, it elevates leadership strategy as a superordinate resource, with dynamic resource orchestration, rather than resource base, as the differentiating factor that sets resilient organisations apart in systemic disruptions. The present study utilised the lenses of DROV to mine the perspectives of 13 Kenyan ex-bankers on dynamic resource orchestration at the intersection of strategy-induced organisational resilience. The results provided empirical validation of the robustness of DROV in explaining strategy-induced organisational resilience, with dynamic resource orchestration as a source of differentiation for sustainable competitive advantage (SCA). The study has effectively contributed to strategic management scholarship by underscoring the critical role of leadership strategy, decisions and actions in the organisational resilience– SCA equation. It has also highlighted the attributes that characterise high-resilience organisations (prospering or capitalising organisations), moderate-resilience organisations (surviving organisations) and low-resilience organisations (struggling organisations). A conceptual illustration for deepening research on the novelty, dimensionality and utility of DROV is provided